Electropysiologic evaluation of the visual pathway in patients with multiple sclerosis - Rodriguez-Mena, Diego; Almarcegui, Carmen; Dolz, Isabel; Herrero, Raquel; Bambo, Maria P; Fernandez, Javier; Pablo, Luis E; Garcia-Martin, Elena (Journal of clinical neurophysiology, 2013)
To evaluate the ability of visual evoked potentials and pattern electroretinograms (PERG) to detect subclinical axonal damage in patients during the early diagnostic stage of multiple sclerosis (MS). The authors also compared the ability of optical coherence tomography (OCT), PERG, and visual evoked potentials to detect axonal loss in MS patients and correlated the functional and structural properties of the retinal nerve fiber layer. Two hundred twenty-eight eyes of 114 subjects (57 MS patients and 57 age- and sex-matched healthy controls) were included. The visual pathway was evaluated based on functional and structural assessments. All patients underwent a complete ophthalmic examination that included assessment of visual acuity, ocular motility, intraocular pressure, visual field, papillary morphology, OCT, visual evoked potentials, and PERG. Visual evoked potentials (P100 latency and amplitude), PERG (N95 amplitude and N95/P50 ratio), and OCT parameters differed significantly between MS patients and healthy subjects. Moderate significant correlations were found between visual evoked potentials or PERG parameters and OCT measurements. Axonal damage in ganglion cells of the visual pathway can be detected based on structural measures provided by OCT in MS patients and by the N95 component and N95/P50 index of PERG, thus providing good correlation between function and structure.